The Causality of Casualness in the Translations of World Poetry: Jorie Graham vs Mary Oliver in Italy (TEST Ticontre. Theory Text Translation, 2014)
The essay explores the impact of poetry translation on the circulation of the works of American poets in Italy. The research is conducted by means of a double approach: in the first place, the aesthetic and cultural value of the poetry of two American women poets (Jorie Graham and Mary Oliver) is assessed, whose work has received a radically different reception. Secondly, the reasons for this disparity of treatment are sought in the interrelation between the practices and activity of poetry translation and of publication, as they are customarily led in Italy. These are inferred from sample interviews with professionals in both fields. The results of the investigation highlight a combination of the casual and the causal, the causing factor being the occasional encounter of a poet with a translator, who then chooses his/her author, texts, and translating strategies according to his/her personal aesthetic, and sometimes ideological, judgment. Il saggio offre un’analisi dell’influenza delle traduzioni sulla circolazione della poesia americana contemporanea in Italia. La ricerca si articola in due momenti: in primo luogo viene fornita una valutazione estetica e culturale dell’opera di due poetesse americane, Jorie Graham e Mary Oliver, la cui ricezione in Italia è particolarmente significativa perché sta conoscendo fortune opposte; in secondo luogo viene condotta un’indagine dei motivi di questa disparità di trattamento nell’interazione tra le pratiche di traduzione e le dinamiche di pubblicazione in atto in Italia. Queste sono state dedotte da alcune interviste campione con professionisti dei due campi. I risultati hanno evidenziato una combinazione di fattori casuali e causali, nella quale l’incontro personale e a volte fortuito tra un poeta e un traduttore mette in moto strategie di selezione e di traduzione motivate da ragioni estetiche e a volte ideologiche.